POPULASI BEKANTAN (Nasalis larvatus) DI SUAKA MARGASATWA KUALA LUPAK, KALIMANTAN SELATAN, INDONESIA - Mila Rabiati; Agus Priyono Kartono; Burhanuddin Masyud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Kuala Lupak Wildlife Sanctuary (KLWS) is one of the proboscis monkey habitat in South Kalimantan. Degradation of habitat due to conversion of mangroves into cultivation area in KLWS is currently the main factor that threaten the sustainability of proboscis monkeys population in this region. This research was conducted to estimate proboscis monkey populations and identified its structure and social groups at KLWS. Proboscis population data were collected by concentration count method. Data collection carried out in three areas: 1) good vegetation and preferably proboscis monkeys area as reference site, 2) vegetated but less favored proboscis area as model 1 site, and 3) disturbed vegetation area, where near from settlement as model 2 site. There were no proboscis found on model site 2. Population estimate of proboscis monkey are 139 ± 43 individuals with the density of 81 individuals/km2. The sex ratio of adult proboscis are 1:3,09. There are three types of social groups proboscis monkey in SMKL i.e. All Male Group (AMG) formed by young males, One Male Group (OMG) consisting of one male and several females with their offspring, abd multimale group formed by two or more OMG’s. There are at least 2 AMG group consisting of 5-26 individual young males, 7 harem’s or OMG’s group consisting of 7-35 individuals, and 8 multimale group with total membership of 9-59 individuals. Proboscis population structure based on age class showed that infant population was smaller than the juvenile and the adult. Keywords: group structure, population, population structure, proboscis monkey, sex ratio